INTERACTIVE ANDROID APPLICATION FOR EDUCATION IN AC-TO-DC CONVERTERS - Landi, Gustavo P. [UNESP]; Goncalves, Flavio A. S. [UNESP]; Marafao, Fernando P. [UNESP]; Paredes, Helmo K. M. [UNESP]; IEEE (Ieee, 2017)
The paper presents an Android application with a friendly and interactive approach to aid the teaching of AC-to-DC converters operating in steady-state. Some features of the proposed application are demonstrated through examples, and forms of integration in teaching activities are addressed.
Keywords: Android; AC-to-DC Converter; Application Learning Tool; Steady-state Simulation